Intracranial Haemorrhage in Patients with Congenital Bleeding Disorders - Humera Siddique , Tahira Zafar ,Tazeen Anwar , Naila Yaqoob (Journal of Rawalpindi Medical College, 2014)
Background To study patients with congenital bleeding disorders presenting with intracranial haemorrhage in relation to the severity of bleeding disorder, presenting features, diagnosis, management and complications. Methods: This descriptive study included all the patients who presented with intracranial bleed. Age, gender, type and severity of bleeding disorder, presence of inhibitor, history of trauma, presenting symptoms and signs, diagnosis, management and complications were documented. Results: Out of 659 registered patients, twenty one presented with twenty three episodes of intracranial haemorrhage. Majority of the patients, presenting with intracranial bleed were of Haemophilia A (61.9%). Intracranial haemorrhage was confirmed by computed tomography except in one case that died immediately after arrival at the centre. Headache(85.7%), vomiting (71.4%) and seizures ( 38.1%) were common presentations. Conclusion: Intracranial haemorrhage needs an index of suspicion in patients with bleeding disorders who present with headaches. As adequate treatment prevents morbidity and mortality, efforts should be made for provision of factor concentrates to ensure adequate management.